Assessment of physicochemical and heavy metals analysis of Erinle Dam Reservoir Water, Osun State, Nigeria - Sangoremi, Abidemi; Adeyeye, Joseph Adeleke; Adeleke, Adebayo Emmanuel; Akinremi, John Omodara; Akintan, Oluwakemi Bolanle; Faloye, Temitope Oluwaseun (FUDMA Journal of Sciences, 2026)
A dam reservoir plays a vital role in the global freshwater supply. This study evaluates the water quality of Erinle Dam Reservoir in Osun State, Nigeria, recognizing the essential importance of clean water for human health and well-being, agriculture, industry, and overall environmental sustainability, especially amid increasing pollution threats. The research aims to assess physicochemical parameters such as pH, temperature, turbidity, dissolved oxygen (DO), biochemical oxygen demand (BOD), total dissolved solids (TDS), and electrical conductivity (EC), examine bacteriological indicators like Escherichia coli, analyze heavy metal concentrations including zinc, cadmium, copper, lead, manganese, arsenic, iron, and chromium, and compare findings with WHO standards. It also seeks to identify pollution sources and recommend strategies for improving water quality. Twelve (12) water samples were systematically collected from different points across the reservoir and analyzed using the WHO and APHA standard laboratory procedures. Descriptive statistical analysis showed that parameters such as pH, temperature, and EC generally remained within acceptable limits; however, levels of cadmium, arsenic, and lead significantly exceeded WHO permissible limits, with calculated high heavy-metal health index risks for the users. Additionally, microbiological tests consistently detected high levels of E. coli in all samples, indicating widespread fecal contamination likely from agricultural runoff, industrial discharges, and domestic waste. Principal Component Analysis (PCA) highlighted spatial variations and pollution trends across sampling sites. The findings emphasize the urgent need for improved water quality monitoring, pollution control measures, and informed policy making to ensure sustainable water resource management in the region.